2014
DOI: 10.1021/om500550a
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion between Ruthenacyclohexadiene and Ruthenabenzene: A Combined Experimental and Theoretical Study

Abstract: Treatment of ruthenabenzene [(C 9 H 6 NO)Ru{CC-(PPh 3 )CHC(PPh 3 )CH}(C 9 H 6 NO)(PPh 3 )]Cl 2 (1) with NaBH 4 produces the first ruthenacyclohexa-1,4-diene [(C 9 H 6 NO)Ru{CC-(PPh 3 )CH 2 C(PPh 3 )CH}(C 9 H 6 NO)(PPh 3 )]Cl (2), which was fully characterized. Under an oxygen atmosphere, complex 2 can easily convert to complex 1. DFT calculations were carried out to rationalize the high regioselectivity in the reaction of the ruthenabenene 1 with NaBH 4 and the interconversion between 1 and 2. ■ INTRODUCTIONMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…[85][86][87] Metallabenzenes of one second row transition metal, ruthenium, are also known. [88][89][90][91][92][93][94] Although theoretically feasible, [16,18,95,96] the isolation of simple metallabenzenes containing other transition metals,p articularly those in the first row, has remained elusive.…”
Section: Metallabenzenesmentioning
confidence: 99%
See 3 more Smart Citations
“…[85][86][87] Metallabenzenes of one second row transition metal, ruthenium, are also known. [88][89][90][91][92][93][94] Although theoretically feasible, [16,18,95,96] the isolation of simple metallabenzenes containing other transition metals,p articularly those in the first row, has remained elusive.…”
Section: Metallabenzenesmentioning
confidence: 99%
“…They are dependent on (but do not have ac lear correlation with changes in) the metal, ligands, charge and ring substituents. [16,86,[100][101][102] Through other computational studies, metallabenzenes have been shown to exhibit negative nucleus-independent chemical shift (NICS) values, [60,94,96,97] diatropic ring currents [96,103,104] and relatively large absolute hardness, [100,105] each of whichi sc onsistent with aromaticity.I th as been noted, however,t hat many of these latter methods may have limited applicability to met-allabenzenes due to the influence of the ancillary ligands and metal anisotropy. [18,97] Although many metallabenzenes have an early planar structure, ac onsiderable number do not.…”
Section: Metallabenzenesmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of chloride to the vinylphosphonium salt group followed by elimination of triphenylphosphine affords the osmabenzene. The interconversion of ruthenabenzene 730 and ruthenacyclohexadiene 731 was studied experimentally and computationally[976]. Treatment of the dicationic complex 730 with sodium borohydride led to the ruthenacyclohexadiene complex 731 as the exclusive regioisomer in the reaction.…”
mentioning
confidence: 99%